2013
DOI: 10.7314/apjcp.2013.14.12.7509
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Duration and Cancer Risk: a Systematic Review and Meta-analysis of Prospective Studies

Abstract: To assess the risk of cancers associated with sleep duration using meta-analysis of published cohort studies, we performed a comprehensive search using PubMed, Embase and Web of Science through October 2013. We combined hazard ratios (HRs) from individual studies using meta-analysis approaches. A random effect dose-response analysis was used to evaluate the relationship between sleep duration and cancer risk. Subgroup analyses and sensitivity analyses were also performed. Publication bias was evaluated using F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
54
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 43 publications
(53 reference statements)
6
54
1
Order By: Relevance
“…22 A meta-analysis investigating the association between sleep duration and cancer risk (skin cancer was not included) found a positive association for colorectal cancer and a negative association for hormone-related cancers such as those of the breast. 23 However, a recent study found no clear relationship between sleep duration and melanoma. 6 In the current study, we controlled for menopausal status and hormone use.…”
Section: Discussionmentioning
confidence: 97%
“…22 A meta-analysis investigating the association between sleep duration and cancer risk (skin cancer was not included) found a positive association for colorectal cancer and a negative association for hormone-related cancers such as those of the breast. 23 However, a recent study found no clear relationship between sleep duration and melanoma. 6 In the current study, we controlled for menopausal status and hormone use.…”
Section: Discussionmentioning
confidence: 97%
“…This interest has been fueled by the fact that over a third of the U.S. population reports insufficient sleep [4] and mounting scientific evidence that sleep disturbances are associated with increased risks of a number of chronic health conditions, including cardiovascular disease, diabetes, and cancer [5-13]. To date, the limited number of published studies on sleep duration and cancer risk have yielded provocative, yet highly inconsistent results, reporting elevated risks associated with both short and long sleep durations as well as no associations for a variety of cancer sites [14-31].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the limited number of published studies on sleep duration and cancer risk have yielded provocative, yet highly inconsistent results, reporting elevated risks associated with both short and long sleep durations as well as no associations for a variety of cancer sites [14-31]. These inconsistencies may partially be a reflection of different mechanistic pathways operating for different cancer sites [13]. The objective of the current study was to conduct an analysis of sleep duration and risk of all cancer sites combined, as well as for the five most commonly-diagnosed cancer sites among a large, prospective cohort of California women.…”
Section: Introductionmentioning
confidence: 99%
“…Although two systematic reviews have supported an association between duration of sleep and risk of cancer [13,14], a review by Lu et al refuted an overall association [15], not excluding the existence of a positive association in specific cancer subtypes. Although most studies that assessed the association between SDB and cancer supported a positive association [16][17][18][19][20], evidence contrary to this also exists [21].…”
Section: Introductionmentioning
confidence: 99%